A holistic perspective to predict yoga tourists’ revisit intention: An integration of the TPB and ECM model - Leou, Eusebio C.; Wang, Huiqing (Frontiers in Psychology, 2023)
The purpose of this study is to empirically investigate the pattern of visitors’ revisiting behavioral intention via the innovational approach of Theory of Planned Behavior (TPB) and the Expectation Confirmation Theory (ECT). This research was conducted by data collection with structured questionnaires as its instrument, which was distributed among 420 yoga tourism visitors in two destinations, Mysore and Rishikesh in India. Collected data had been processed by confirmatory factor analysis and structural equation modeling. The data analysis results showed that the behavioral attitude of yoga tourism visitors can mediate the influence of behavioral intention through the satisfaction. The findings of this study include the following points: (1) the components of attitude, subjective norm and destination image apply a direct effect on the cultural & spiritual experiences of yoga tourism visitors; (2) cultural & spiritual experiences have a direct effect on the expectation confirmation and the satisfaction of yoga tourism visitors; (3) Expectation confirmation has a direct effect on the satisfaction and the revisit behavioral intention of yoga tourism visitors; (4) Satisfaction has a direct effect on the revisit behavioral intention of yoga tourism visitors. This study contributed by examining the satisfaction and revisit intentions of yoga tourism visitors through an integrated study of planning behavior and expectation confirmation models, which might be refilling the scarcity of research in the tourism literature. The result of this study might offer important implications for scholars, marketers, and tourism industry to better serve this emerging niche market.